The Interplay of Motivation, Self-Efficacy, and Critical Thinking in Predicting Reading Literacy: A Multivariate Analysis of Indonesian Elementary Students - Purnamasari S, Ayu; Pama, Violeta Inayah; Nurhayati, Nurhayati (Jurnal Pendidikan Progresif, 2025)
The Interplay of Motivation, Self-Efficacy, and Critical Thinking in Predicting Reading Literacy: A Multivariate Analysis of Indonesian Elementary Students. The poor performance of Indonesian students in international tests such as PISA underscores the imperative of improving early reading competency. Objectives: This study evaluates the impact of motivation, self-efficacy, and critical thinking on reading literacy among elementary school students. Reading literacy is a fundamental skill for improving educational attainment and social performance. At the same time, motivation, self-efficacy, and critical thinking are identified as the fundamental psychological and cognitive factors influencing students' reading success. Methods: The study used a quantitative, descriptive-correlational design. The students in the population were selected using stratified random sampling to ensure the sample was as balanced as possible among the fifth-grade elementary school students who participated in the study. Standardized questionnaires assessing motivation and self-efficacy, as well as structured tests assessing critical thinking and reading literacy, were used to collect data. Data were analyzed using Pearson’s correlation test and multiple regression to examine the combined and partial effects of the predictors on reading literacy scores. Findings: Motivation, self-efficacy, and critical thinking concurrently accounted for 65% of the variance in students' academic performance, indicating a strong impact on reading literacy. Partial influence was found to have the greatest impact on self-efficacy (Beta=0.40), followed by motivation (Beta=0.35) and critical thinking (Beta=0.30). The results suggest that self-confidence, motivation, and critical thinking skills are associated with better literacy performance, as students are more likely to meet the minimum reading literacy level. Conclusion: The research also underscores the importance of integrating motivation, self-efficacy, and critical thinking into literacy instruction. Educators and curriculum developers should develop curricula and design learning programs that, through instruction, improve students' confidence, intrinsic motivation, and analytical thinking. These efforts will help strengthen reading literacy at the elementary school level, address literacy challenges that continue to plague Indonesia, and, in the long term, prepare students for academic and social success. Keywords: self-efficacy, critical thinking, Motivation, reading literacy.